Riding the Lines and Overwriting in the Margins: Affect and Multimodal Literacy Practices. (September 2016) - Lenters, Kimberly
This case study examines the multimodal literacy practices of 11-year-old Nigel as he plays with assemblages of people, objects, and practices in his storywriting. The study asks "How does following the seemingly off-task multimodal literacy practices of one pre-adolescent youth across his home-community-school terrain provide insight into contemporary literacy learning and instruction?" Using assemblage theory, the article maps a period in time, the early months of his fifth-grade experience, when one boy approached the literacies privileged in his classroom with what appeared to be a certain amount of disregard, while engaging in personal literacy practices that were both rich and, at times, subversive. The analysis maps the people, signs, material objects, events, and places in the unfolding of Nigel's play with two symbolic figures, the line rider and the stick man. Viewed across time and place, Nigel's textual and embodied play with these figures demonstrate ways a young adolescent, fully immersed in and engaged with his digital and material world, "overwrites" official texts and produces rich stories that go unnoticed by the adults around him. This unfolding took place in unpredictable ways, and as it occurred, literacy practices that brought intellectual and visceral engagement, pleasure and pride, and agentive recourse to Nigel in his practice of literacy came into focus. The emergence of Nigel's inscriptions across multiple terrains provides insight into ways in which a socio-material perspective, with its focus on the role of affect and the body, may assist us in re-thinking multimodal writing development.